2020
DOI: 10.21203/rs.3.rs-36856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Professionals Tinker With Ethical Tensions Collectively When Fostering Service User Autonomy: An Ethnographic Study In Long-term Care

Abstract: Background: The value of patient autonomy has become central in healthcare. However, care practices involve a plurality of possibly conflicting values. These values often transgress the borders of the individual professional-client relationship as they involve family members, other professionals and community organizations. Good care should acknowledge this complexity, which requires a collective handling of the tensions between values. To better understand this process, we draw on Mol (2008, 2010) by developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For T A B L E 2 Main connections between the senses and the views. 42,43 As such, the intricate relationships underscore the potential for conflicts, emphasizing the complexity that partners face in navigating collaboration in care triads.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For T A B L E 2 Main connections between the senses and the views. 42,43 As such, the intricate relationships underscore the potential for conflicts, emphasizing the complexity that partners face in navigating collaboration in care triads.…”
Section: Discussionmentioning
confidence: 99%
“…Also, each care triad may comprise different care professionals and informal caregivers, making it even more challenging for partners in the care triad to assume a role that acknowledges and accommodates all views involved. Previous studies revealed that beneath these different needs and experiences often lie diverse values and that these values may come into conflict 42,43 . As such, the intricate relationships underscore the potential for conflicts, emphasizing the complexity that partners face in navigating collaboration in care triads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations